An update on the use of degarelix in the treatment of advanced hormone-dependent prostate cancer - Rick, Ferenc G (Dove Medical Press, 2013)
Androgen deprivation therapy remains the mainstay of medical treatment for advanced prostate cancer. Commonly, this is achieved with medical androgen deprivation rather than surgical intervention as the permanence and psychological effects of the latter are unacceptable for most patients. Degarelix is a third generation antagonist of luteinizing hormone-releasing hormone (LHRH, also termed gonadotropin-releasing hormone) for the first-line treatment of androgen-dependent advanced prostate cancer. Degarelix acts directly on the pituitary receptors for LHRH, blocking the action of endogenous LHRH. The use of degarelix eliminates the initial undesirable surge in gonadotropin and testosterone levels, which is produced by agonists of LHRH. Degarelix is the most comprehensively studied and widely available LHRH antagonist worldwide. Clinical trials have demonstrated that degarelix has a long-term efficacy similar to the LHRH agonist leuprolide in achieving testosterone suppression in patients with prostate cancer. Degarelix, however, produces a faster suppression of testosterone and prostate-specific antigen (PSA), with no testosterone surges or microsurges, and thus prevents the risk of clinical flare in advanced disease. Recent clinical trials demonstrated that treatment with degarelix results in improved disease control when compared with an LHRH agonist in terms of superior PSA progression-free survival, suggesting that degarelix likely delays progression to castration-resistant disease and has a more significant impact on bone serum alkaline phosphatase and follicle-stimulating hormone. Degarelix is usually well tolerated, with limited toxicity and no evidence of systemic allergic reactions in clinical studies. Degarelix thus represents an important addition to the hormonal armamentarium for therapy of advanced androgen-dependent prostate cancer.